The electrical properties of ruthenium-aluminium alloys - Smith, Ernest Gregory (Centre for Materials Engineering, 2016)
The electrical properties of platinum, gold-palladium and a selection of alloys from the ruthenium-aluminium system have been studied at high temperatures (up to 1000°C). The majority of the ruthenium-aluminium alloy compositions studied lie near or in the ruthenium aluminide phase field. Ruthenium aluminide is a B2 structure intermetallic which is suited to high temperature applications because in addition to a high melting point (2060°C), oxidation resistance to 1200°C and high temperature strength, it is also relatively ductile at room temperature. The possibility of high temperature electrical applications required an investigation of the electrical properties of ruthenium-aluminium alloys as compared to platinum and gold-palladium. Two sets of apparatus, capable of measuring the resistivity and thermo-e.m.f to high temperatures, were constructed and used to obtain the first experimental results for the electrical properties of ruthenium-aluminium alloys. Chemical analysis of these alloys has been performed for the first time, and together with energy dispersive spectroscopy, has revealed a composition at which there is a resistivity minimum and a positive thermo-e.m.f maximum, which appears to be associated with the formation of the ordered ruthenium aluminide phase. The resistivity and the temperature dependence of resistivity of some ruthenium-aluminium alloys are similar to that of platinum, the least resistive of the three materials investigated.